Sosialisasi dan Pelatihan Kesehatan dan Keselamatan Kerja (K3) Teknisi Elevator dan Eskalator di PT Pratama Mitra Sejati Jakarta - Arief Suardi Nur Chairat; Vendy Antono; Dyah Pratiwi Kusumastuti; Tri Wahyu Oktaviani Putri (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
Occupational health and safety (OHS) in every business is the most important factor in order to create a safe and comfortable atmosphere in the work environment so as to increase performance productivity and achieve the business vision and mission. However, the lack of understanding and awareness in applying OHS to every worker, especially technicians who work with high risk, needs special attention. To overcome this, community service activities were carried out in the form of OHS socialization and training for technicians, especially elevator and escalator technicians. OHS socialization and training for elevator and escalator technicians carried out for 2 days with material on elevator and escalator OHS regulations, elevator and escalator operation and maintenance and rescue procedures aimed at increasing the knowledge of each technician. The results of the socialization and training activities showed an increase in understanding of OHS as seen from changes in technician behavior, especially awareness in maintaining the safety of oneself and others in the work environment by using personal protective equipment and complying with safety rules and signs.